ANALISIS SENSITIVITAS PARAMETER INJEKSI GAS LIFT TERHADAP PERFORMA PRODUKSI SUMUR FT - Ananda, farhan; Abror, Hadziqul (JSED, 2025)
Well FT is a multilayer oil well that is no longer able to produce under natural flow conditions due to insufficient reservoir pressure, as indicated by the absence of an intersection between the Inflow Performance Relationship (IPR) and Vertical Lift Performance (VLP) curves. To restore and optimize production, a continuous gas lift system was designed and evaluated using nodal analysis and PIPESIM simulation. The gas lift design successfully reduced the fluid column density in the tubing, lowered the bottom-hole flowing pressure (Pwf), and shifted the VLP curve to intersect with the IPR curve, enabling stable production. Sensitivity analysis was performed on key operating parameters, including gas injection rate, injection pressure, and injection depth, to determine the optimum operating conditions. The results show that an optimum gas injection rate of 3 MMSCFD provides the most effective production increase before efficiency declines. Deeper gas injection further enhances production by reducing Pwf, while an injection pressure of 600 psia was identified as the optimal condition, offering near-maximum production with improved operational stability. Overall, the implementation of continuous gas lift proved to be technically effective for enhancing the production performance of Well FT.